2015
DOI: 10.1093/infdis/jiv460
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Epitope–Specific CD8+T Cells and Interferon Signaling Intersect in Chronic Hepatitis C Virus Infection

Abstract: CD8(+) T cells specific to caspase-cleaved antigens derived from apoptotic T cells represent a principal player in chronic immune activation. Here, we found that both apoptotic epitope-specific and hepatitis C virus (HCV)-specific CD8(+) T cells were mostly confined within the effector memory (EM) or terminally differentiated EM CD45RA(+) cell subsets expressing a dysfunctional T-helper 1-like signature program in chronic HCV infection. However, apoptotic epitope-specific CD8(+) T cells produced tumor necrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…Recent work has also correlated intrahepatic activated HCV‐specific and polyclonal epitope‐specific (not HCV‐specific) CD8 + T cells with chronic inflammation during infection, measured by aspartate aminotransferase/alanine aminotransferase elevation and IFN‐stimulated gene transcript expression, with the suggestion that this contributes to fibrosis progression . We were unable to perform staining with Eomes/T‐bet to assess the balance of functional and dysfunctional cells in our study due to sample availability.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recent work has also correlated intrahepatic activated HCV‐specific and polyclonal epitope‐specific (not HCV‐specific) CD8 + T cells with chronic inflammation during infection, measured by aspartate aminotransferase/alanine aminotransferase elevation and IFN‐stimulated gene transcript expression, with the suggestion that this contributes to fibrosis progression . We were unable to perform staining with Eomes/T‐bet to assess the balance of functional and dysfunctional cells in our study due to sample availability.…”
Section: Discussionmentioning
confidence: 95%
“…Recent work has also correlated intrahepatic activated HCV-specific and polyclonal epitope-specific (not HCV-specific) CD8 1 T cells with chronic inflammation during infection, measured by aspartate aminotransferase/alanine aminotransferase elevation and IFN-stimulated gene transcript expression, with the suggestion that this contributes to fibrosis progression. (25) We were unable to perform staining with Eomes/T-bet to assess the balance of functional and dysfunctional cells in our study due to sample availability. Because most CD8 1 T cells in the liver are not HCV-specific, we suspect that the increase in peripheral CD8 1 T-cell concentrations observed during therapy likely primarily reflects HCV-nonspecific CD8 1 T cells drawn to the liver as a result of chronic inflammation and chemokine production, (26) a hypothesis that can be assessed in future work.…”
Section: Discussionmentioning
confidence: 98%
“…principally converting tolerogenic into stimulatory dendritic cells (DCs) [32][33][34][35][38][39][40][41][42] . Then, DCs acquire high capability to migrate, to phagocytose dying cells, to process more efficiently caspase-cleaved cellular proteins (i.e., NM-neoAgs), and to cross-prime CD8 + T cells that can provide tumor control 35,38,41,42 , on the one hand, and immunopathology in various forms of chronic inflammatory diseases, on the other hand 37,[43][44][45][46][47][48] . In addition, several studies found that ICD synergizes with ICB therapy to further improve T cell responses against different tumors, proposing hence the hypothesis that ICD converts tumor cells into endogenous vaccine and boosts the ICB effects [49][50][51][52][53][54] .…”
mentioning
confidence: 99%
“…16 Among the tested ISGs, we noticed that ISG15 expression was more variable among patients at baseline (day 0) compared to Protein Kinase R (PKR) and Myxovirus resistance protein 1 (MXA) (Figure 1a), in line with previous data. 9 Indeed, the standard deviation (SD) of ISG15 was 0.265, higher than the SD of MXA (0.033), and of PKR (0.071). Therefore, we stratified patients into ISG15 lo or ISG15 hi depending on the expression level of ISG15 mRNA in total PBMCs with respect to the average value as cut-off.…”
Section: Isg15 Induction Correlates With Reduced Treg Depletion In Chmentioning
confidence: 85%
“…5,6 However, ISG15 displays several immunomodulatory functions: for instance, in chronic hepatitis C (CHC), a persistent expression of ISG15 is responsible for resistance to IFN-based therapy and contributes to limit inflammation. [7][8][9][10] Notably, humans with inherited ISG15 deficiency display pathological signs of hypersensitivity to type I IFNs: indeed, in humans, free intracellular ISG15 binds and stabilises Ubiquitin Specific Peptidase 18 (USP18), a negative regulator of type I IFN signalling pathway. 11 An elevated IFN signature and increased STAT1 phosphorylation in monocytes were probably responsible for driving inflammation in ISG15-deficient subjects.…”
Section: Introductionmentioning
confidence: 99%